Analysis of Indonesia Confucians Understanding Towards Religious Doctrines and Ordinances in Confucianism - Sugiato Lim (Bina Nusantara University, 2013)
To a great extent, daily life of Indonesia Chinese community is filled with religious overtones. This paper basically analyzes the understanding of Indonesia Confucians towards their religion. The first part of this paper will be discussing about the general definition of religion and its religious elements. The second part will analyze the understanding of Indonesia Confucians towards their religious doctrines and ordinances respectively. In conclusion, overview regarding Indonesia Confucians and a special historical background of Indonesia Confucianism, which consists of its formation and development as a legal religion in line with Indonesia national conditions, social conditions and characteristic, will be presented.